Comparing the Effectiveness of Natural and Synthetic Emulsifiers on Oxidative and Physical Stability of Avocado Oil-Based Nanoemulsions - Arancibia-Aguilar, C; Matiacevich, S; Riquelme-Hinojosa, N (Elsevier Ltd, 2017)
Food industries search for replace synthetic surfactant with natural ingredients, but emulsifier type has an impact on lipid oxidation and stability of emulsions. The aim of the study was to evaluate the emulsifier type and concentration effect on avocado oil-based nanoemulsion development, specifically on physical and oxidative stability. O/W nanoemulsions were prepared with 10% avocado oil using natural (lecithin) and synthetic (Tween 80) emulsifiers at different concentrations (2.5–10%). Results showed that nanoemulsions exhibited anionic (Z-potential: − 26 to − 59 mV) lipid droplets with particle size between 103 and 249 nm. Emulsifier type and concentration affected physical stability, being the most stable at 7.5–10% Tween 80 (15 days) and 7.5–10% lecithin (10 days). Meanwhile, emulsifier concentration affected oxidative stability of nanoemulsions, being the most unstable at 2.5% Tween 80 and 10% lecithin. Finally, although Tween 80 was more effective than lecithin, it also could be used to develop natural nanoemulsions with good physical properties. © 2017 Elsevier Ltd